Synthesis: An Interdisciplinary Discipline. - Tow, Bruce L.; Gilliam, David A. (Futurist)
As the professional world becomes increasingly specialized, the time has come for leaders to adopt a multidiscipliary approach to problem solving. Specialization has not been a planned or coordinated process, so there are large knowledge gaps between specialties. The ideal solution to this problem would take advantage of the benefits inherent in specialization while avoiding the pitfalls. Ideally, when confronted with a multidisciplinary problem, there would be someone who could ascertain which combination of specialties is likely to solve the problem, organize a team, motivate the individuals to operate as a group toward a solution to the problem, and ensure effective communication between specialists. If enough individuals attempt this approach and train others to do so, it will become a recognized discipline known as synthesis.